1988
DOI: 10.7164/antibiotics.41.1253
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of deoxyspergualin in autoimmune disease mice.

Abstract: An assessment of the prophylactic and ameliorative effects of deoxyspergualin (NKT-01), an immunosuppressive agent, was carried out in male MRL/MpJ-lpr/lpr (MRL/1) mice which spontaneously develop lupus-like lesions. When NKT-01 was administered ip daily from the age of either 8 or 19 weeks, diseases such as massive lymphadenopathy, circulating anti-DNA antibody and lupus nephritis were markedly suppressed. The primary response to lipopolysaccharide was significantly reduced in MRL/1mice administered NKT-01but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In agreement with these experimental observations, clinical studies in human have demonstrated that DSG reverse kidney [32,33] and liver [34] allograft rejection. Also, DSG has been effective in decreasing the severity of autoimmune diseases and GVHD [35,36]. However, in spite of these numerous studies, the precise mechanism of action of DSG is unsettled.…”
Section: Discussionmentioning
confidence: 98%
“…In agreement with these experimental observations, clinical studies in human have demonstrated that DSG reverse kidney [32,33] and liver [34] allograft rejection. Also, DSG has been effective in decreasing the severity of autoimmune diseases and GVHD [35,36]. However, in spite of these numerous studies, the precise mechanism of action of DSG is unsettled.…”
Section: Discussionmentioning
confidence: 98%
“…Since its discovery, DSG has been widely studied and demonstrated efficacy first as an anticancer agent, then in animal transplantation either in allografts or xenografts, and more recently in graft-versus-host disease (GVHD) animal models . DSG has also been widely investigated in autoimmune diseases. The high potential of DSG to reverse renal graft rejection was first reported in 1990 .…”
Section: Introductionmentioning
confidence: 99%
“…If the autopsy disclosed abnormal findings such as hydronephrosis and infection, the animal was excluded from the experimental group. Deoxyspergualin (DSG), an analogue of spergualin, is produced as a metabolite by Bacillus laterosporus [18] and has been confirmed to have a strong immunosuppressive effect in various transplantation models including mice [15], rats [23], dogs [l], monkeys [4], and humans [2]. The mechanism of action of DSG has not been clarified yet, but some reports have shown that DSG has a totally different mechanism of action [5] than newly developed, potent immunosuppressive drugs such as cyclosporin (CyA) [7], FK 506 [20], or OKT3 monoclonal antibody [3].…”
Section: Renal Transplantationmentioning
confidence: 99%